Adaptive Structured Pickering Emulsions and Porous Materials Based on Cellulose Nanocrystal Surfactants. Issue 41 (19th September 2018) - Li, Yanan; Liu, Xubo; Zhang, Zhen; Zhao, Shaojie; Tian, Guifang; Zheng, Jinkai; Wang, Dong; Shi, Shaowei; Russell, Thomas P.
Abstract: Taking advantage of the formation and assembly of cellulose nanocrystal surfactants (CNCSs) at the water–oil interface, where polar cellulose nanocrystals (CNCs) and end‐functionalized polymer chains interact, the preparation and stability of emulsions prepared with CNCSs were investigated. The packing density of CNCSs at the interface can be adjusted by tuning parameters such as pH, ionic strength, and concentration/molecular weight of the end‐functionalized polymer ligands. Stable non‐spherical emulsions are obtained during homogenization, as a result of the interfacial jamming of CNCSs, with pH‐triggered reconfigurability. Porous materials are prepared by freeze‐drying creamed, CNCS‐stabilized emulsions. The cells of the porous materials have a controlled pore size and shape that are commensurate with the droplets in the emulsion and are responsive to pH. The behavior of the adaptive, reconfigurable supracolloidal system is coupled to its internal and surrounding environment. Abstract : The stability of emulsions prepared at the water–oil interface with cellulose nanocrystal surfactants (CNCSs) were investigated. The packing density can be adjusted by tuning parameters such as pH, ionic strength, and concentration/molecular weight of the end‐functionalized polymer ligands. Stable non‐spherical emulsions are obtained during homogenization with pH‐triggered reconfigurability. Porous materials are prepared by freeze‐drying.